Essentials of contemporary management - Jones, Gareth R.; George, Jennifer M. (New York : McGraw Hill Education, 2015)
In this sixth edition of essentials of contemporary management, global edition, we continue to focus on providing the most up-to-date account of the changes taking place in the world of management and management practices while maintaining our emphasis on making our text relevant and interesting to students.
Management and managers -- The environment of management -- Planning, decision making, and competitive advantage -- Organizing and change -- Leading individuals and groups -- Controlling essential activities
Includes bibliographical references and index.
Keywords: MANAGEMENT